The squatters of Dhaka City : dynamism in the life of Agargaon squatters - Paul, Pratima; Mahmud, Simeen; Afsar, Rita. (Dhaka : University Press Ltd., 1996)
Study restricted to Agargaon, Dhaka.
Includes bibliographical references (p. [58]-60).
Keywords: Squatters -- Bangladesh -- Agargaon (Dhaka); Squatters -- Political activity -- Bangladesh -- Agargaon (Dhaka)